Radial Mandibular Coronoidectomy in a Basset Hound as a Treatment for Temporomandibular Joint Dysplasia - Elena Rappa; Bruno Santos; Marie‐Pauline Maurin (Veterinary Medicine and Science)
ABSTRACT A ‐year‐old Basset Hound, previously diagnosed with temporomandibular joint dysplasia, presented with a 6‐month history of pain during mastication and frequent open‐mouth locking episodes. Oral examination under sedation revealed displacement of the mandible to the left and jaw fixation in an open position. Computed tomography images of the head performed in open and closed positions before and after surgery were obtained. A left partial coronoidectomy was performed using a radial TPLO saw blade, removing bone impingement between the coronoid process and zygomatic arch. The dog was eating soft food a couple of hours after surgery, and no further open‐mouth locking episodes or pain associated with mouth opening were reported up to one year postoperatively. Functional results were achieved using this technique, with a rapid patient recovery.